2013
DOI: 10.1016/j.ajpath.2013.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Ranibizumab Is a Potential Prophylaxis for Proliferative Vitreoretinopathy, a Nonangiogenic Blinding Disease

Abstract: Proliferative vitreoretinopathy (PVR) exemplifies a disease that is difficult to predict, lacks effective treatment options, and substantially reduces the quality of life of an individual. Surgery to correct a rhegmatogenous retinal detachment fails primarily because of PVR. Likely mediators of PVR are growth factors in vitreous, which stimulate cells within and behind the retina as an inevitable consequence of a breached retina. Three classes of growth factors [vascular endothelial growth factor A (VEGF-A), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 54 publications
2
45
0
Order By: Relevance
“…On day 28, immediately prior to sacrifice, electroretinogram (ERG) analysis was performed as previously described (41). Following euthanasia, the eyes were enucleated, fixed in 10% formalin, and embedded in paraffin.…”
Section: Figmentioning
confidence: 99%
“…On day 28, immediately prior to sacrifice, electroretinogram (ERG) analysis was performed as previously described (41). Following euthanasia, the eyes were enucleated, fixed in 10% formalin, and embedded in paraffin.…”
Section: Figmentioning
confidence: 99%
“…Figure 1A illustrates our recent discovery that VEGF promotes viability of cells by reducing the level of p53. VEGF accomplishes this by persistently activating monomeric PDGFR␣; this process is independent of VEGFRs and even proceeds in fibroblasts, which express little few any VEGFRs (12,13,22). Although these discoveries were made in the context of a blinding eye disease, we speculated that this VEGF-driven survival mechanism was also relevant to physiology.…”
Section: Resultsmentioning
confidence: 99%
“…Attempts to identify which non-PDGFs are responsible for indirectly activating PDGFR␣ led to the discovery of a hierarchy among the three classes of growth factors that engage PDGFR␣ (12,13). These three classes of growth factors include PDGFs (direct activators), non-PDGFs (indirect activators), and vascular endothelial cell growth factor A (VEGF), which competitively antagonizes PDGF-dependent activation of PDGFR␣ (14).…”
mentioning
confidence: 99%
“…2 Recent studies have shown a strong role for growth factors in the pathogenesis of proliferative vitreoretinopathy (PVR). 3,4 Vascular endothelial cell growth factor (VEGF) A has been reported to be able to activate the platelet-derived growth factor (PDGF) receptor a, a receptor tyrosine kinase that is key to pathogenesis of PVR. 3 Interestingly, Pennock et al 4 reported that ranibizumab protected the rabbits from developing PVR.…”
mentioning
confidence: 99%
“…3,4 Vascular endothelial cell growth factor (VEGF) A has been reported to be able to activate the platelet-derived growth factor (PDGF) receptor a, a receptor tyrosine kinase that is key to pathogenesis of PVR. 3 Interestingly, Pennock et al 4 reported that ranibizumab protected the rabbits from developing PVR. In contrast to these findings, our results showed that intrasilicone injection of bevacizumab does not eliminate the risk of subsequent PVR and may be associated with subretinal proliferation.…”
mentioning
confidence: 99%